Effect of L- Carnitine Supplementation During in vitro Maturation on Oocyte Maturation and Cleavage Rate in Sahiwal Cows - Singh, Khushpreet; Singh, Narinder; Kaur Mavi, Gurjot; Honparkhe, Mrigank; Shekhar, Apoorva; Singh, Prahlad (The Indian Journal of Animal Reproduction, 2025)
The experiment was conducted to study the effect of supplementation of L-Carnitine in maturation media on oocyte  maturation. Cumulus oocyte complexes (COC’s) obtained by follicular aspiration having at least a complete layer of  cumulus cells were randomly divided into two groups containing 10 replicates each of 10-12 oocytes. In vitro matura tion of the COC’s supplementation with 3 mM L-Carnitine showed (Mean± Std. Error; %) significantly lower (p
Keywords: Cleavage rate; Cumulus Oocyte Complexes (COCs); In Vitro Maturation (IVM); L-Carnitine; Ovum Pickup (OPU)